Neonatology practice : made easy - Faridi, MMA (Jaypee Brothers Medical Publishers, 2013)
Improving neonatal survival is crucial for achieving Millennium Development Goal-4. Several good books are available on the subject but in contrast the book is comprehensive, handy and concise. The book starts itself from control measures for infection in NICUs and importance of hand hygiene and then goes ahead to impart both the basic and advanced knowledge for management of almost all common/uncommon clinical situations came across in the neonatology practice. The book is structured with an idea that the medical students or the medical personnel working in the NICU or with neonates get some crisp and to the point on-table information to manage neonatal concerns and to do common procedures in neonatology. Some important annexures which are very useful for day-to-day working in the NICU are also here. Neonatology practice made easy is a quick reference guide to neonatology for paediatricians and neonatologists. Beginning with infection control and the importance of hygiene, the book covers the diagnosis and management of numerous common and less common conditions, including nutrition and weight disorders, respiratory distress, seizures, hypoglycaemia, apnoea, and infections such as hiv, hepatitis b and tuberculosis. Presented in an easy to follow format, this manual provides useful annexures including checklists for resuscitation and emergency drugs, conversions, fluids protocols, a patient discharge form, and extensive references. Key points * practical guide to neonatology for paediatricians and neonatologists * discusses importance of infection control and hygiene * covers diagnosis and treatment of most common and less common diseases and disorders * includes useful annexures for easy reference.